2008
DOI: 10.1073/pnas.0711170105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Plet-1 as a specific marker of early thymic epithelial progenitor cells

Abstract: The thymus is essential for a functional immune system, because the thymic stroma uniquely supports T lymphocyte development. We have previously identified the epithelial progenitor population from which the thymus arises and demonstrated its ability to generate an organized functional thymus upon transplantation. These thymic epithelial progenitor cells (TEPC) are defined by surface determinants recognized by the mAbs MTS20 and MTS24, which were also recently shown to identify keratinocyte progenitor cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 32 publications
2
75
0
Order By: Relevance
“…TECs are unique in that they are highly heterogeneous and, unlike other epithelial cells, are arranged in a three-dimensional network. Several studies have shown that mammary and thymic epithelia express various markers in common (37,38). It is interesting to note that BTN1A1 and BTN2A2 were expressed on TECs at the junction of the cortex and medulla, which is the site where T cell precursors enter the thymus via blood vessels (39).…”
Section: Discussionmentioning
confidence: 99%
“…TECs are unique in that they are highly heterogeneous and, unlike other epithelial cells, are arranged in a three-dimensional network. Several studies have shown that mammary and thymic epithelia express various markers in common (37,38). It is interesting to note that BTN1A1 and BTN2A2 were expressed on TECs at the junction of the cortex and medulla, which is the site where T cell precursors enter the thymus via blood vessels (39).…”
Section: Discussionmentioning
confidence: 99%
“…2A), suggesting that cells with the phenotypes of TEPs [20][21][22] can be generated from mESCs. To determine whether the EpCAM1 þ cells express TEP-associated genes [40,41], EpCAM1 þ and EpCAM1 À cells were purified from the cultures (more than 95% purity) and subjected to real-time quantitative RT-PCR analysis for the expression of Pax1, Pax9, FoxN1, and Plet1. As shown in Figure 2B, although the expression levels of these genes in the mESC-derived EpCAM1 þ cells were lower than those in EpCAM1 þ cells purified from embryonic day (E)-12 thymi, they were significantly higher than those in the mESC-derived EpCAM1 À cells, further indicating that the mESC-derived EpCAM1 þ cells contained TEPs.…”
Section: Differentiation Of Mescs Into Cells Having the Phenotype Of mentioning
confidence: 99%
“…A distinct compartment of the HF residing below the infundibulum and above the bulge region was identified by the presence of the MTS24 surface marker (Figure 1) (25). The gene recognized by MTS24 has now been identified as Plet-1, which encodes a protein of unknown function and may be a marker of progenitor cells in multiple tissues (26). Interestingly, MTS24 + HF cells purified by flow cytometry were highly clonogenic in vitro and exhibited a transcript profile similar to bulge stem cells suggesting that these cells may represent a progenitor cell population in the HF potentially derived from the bulge (25).…”
Section: Cutaneous Epithelium As a Multiple Stem And Progenitor Cell mentioning
confidence: 99%